Association of Anaesthetists of Great Britain and Ireland1: Safe vascular access 2016. (17th February 2016) - Bodenham (Chair), A.; Babu, S.; Bennett, J.; Binks, R.; Fee, P.; Fox, B.; Johnston, A. J.; Klein, A. A.; Langton, J. A.; Mclure, H.; Tighe, S. Q. M.
Summary: Safe vascular access is integral to anaesthetic and critical care practice, but procedures are a frequent source of patient adverse events. Ensuring safe and effective approaches to vascular catheter insertion should be a priority for all practitioners. New technology such as ultrasound and other imaging has increased the number of tools available. This guidance was created using review of current practice and literature, as well as expert opinion. The result is a consensus document which provides practical advice on the safe insertion and removal of vascular access devices.